Vinegar as a disarming agent to prevent further discharge of the nematocyst of the stinging Hydromedusae Olindias sambaquiensis - Mianzan, Hermes Walter (2001)
Olindias sambaquiensis, known as agua viva, is an endemic hydromedusa that is distributed from latitude 23 degrees to 42 degrees south in the southwestern Atlantic Ocean and is known to cause severe stings. This is the first report of the use of vinegar in disarming O sambaquiensis nematocysts and includes preliminary observations on its use in managing the stings of hydromedusae.